2020
DOI: 10.1038/s41416-019-0726-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-derived extracellular vesicles in blood of metastatic cancer patients associate with overall survival

Abstract: BACKGROUND: Circulating tumour cells (CTCs) in blood associate with overall survival (OS) of cancer patients, but they are detected in extremely low numbers. Large tumour-derived extracellular vesicles (tdEVs) in castration-resistant prostate cancer (CRPC) patients are present at around 20 times higher frequencies than CTCs and have equivalent prognostic power. In this study, we explored the presence of tdEVs in other cancers and their association with OS. METHODS:The open-source ACCEPT software was used to au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 65 publications
4
69
0
Order By: Relevance
“…As noted previously, B7-H3 may be a useful prognostic marker for MB patients [ 17 , 74 ]. Interestingly, various cancer models have shown that increased microvesicle and exosome shedding correlates with more aggressive neoplasms [ 75 , 76 , 77 , 78 ]. Since B7-H3 appears to increase exosomal production in D283 cells, further investigation into this relationship may lead to improved understanding of how valuable B7-H3 may be as a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, B7-H3 may be a useful prognostic marker for MB patients [ 17 , 74 ]. Interestingly, various cancer models have shown that increased microvesicle and exosome shedding correlates with more aggressive neoplasms [ 75 , 76 , 77 , 78 ]. Since B7-H3 appears to increase exosomal production in D283 cells, further investigation into this relationship may lead to improved understanding of how valuable B7-H3 may be as a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Values are derived from the literature (5,7,11). The frequency of the large tumor-derived extracellular vesicles (ltdEVs, light green circle) determined in the Cancer-ID program and the small tdEVs (stdEVs, light green square) estimated using the frequency of ltdEVs (8)(9)(10).…”
Section: Cancer-id Specific Methods and Operating Principlementioning
confidence: 99%
“…By the use of affinity-based techniques using antibodies directed to antigens expressed on tumor cells but not on blood cells, we demonstrated the enrichment of large (>1 µm) EpCAM + tdEVs from blood from metastatic cancer patients (8,9). EVs from different origin were eliminated in the enriched sample.…”
Section: Cancer-id Insightsmentioning
confidence: 97%
See 1 more Smart Citation
“…Large tumor-derived extracellular vesicles (tdEVs) are co-isolated with CTCs and are present in an order of magnitude higher frequencies than CTCs [7,8]; thus, they can increase the number of "readable" patient samples for the assessment of therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%